Penerapan SmartContract Berbasis Blockchain Dalam Keuangan Islam: Tinjauan Sistematis - Riska Ayu Wardani; Sri Luayyi; Putri Awalina (Jurnal Proaksi, 2025)
Main Purpose - This study aims to examine the role of blockchain-based smart contracts in building transparency and accountability in Islamic finance.Method - This research employs a qualitative approach using the Systematic Literature Review (SLR) method based on the PRISMA framework. A total of 25 selected articles published between 2020 and 2025 from reputable databases were systematically reviewed.Main Findings - The findings reveal that blockchain and smart contracts enhance transparency through immutable and distributed transaction records. Smart contracts strengthen accountability by automating Shariah-compliant contracts, thus reducing the risks of moral hazard and administrative errors. Nevertheless, the study also highlights challenges such as regulatory limitations, infrastructure readiness, potential gharar, and technical issues like the oracle problem.Theory and Practical Implications - These results reinforce accountability theory by emphasizing the role of technology in ensuring openness and responsibility within Islamic financial institutions. Practically, the study suggests the urgency of establishing comprehensive regulations and the active involvement of Shariah Supervisory Boards in smart contract design.Novelty - This study contributes novelty by systematically examining the effectiveness of blockchain-based smart contracts not only from a technical perspective but also from regulatory, fiqh, and governance viewpoints within the context of Islamic finance.